Critical care nursing the humanised approach - White, Sara Jane (SAGE Publications, Limited, 2024)
Covering the essential aspects of critical care nursing, students are asked to consider the biopsychosocial triggers of critical illness, and are walked through a number of different patient scenarios.
Description based on publisher supplied metadata and other sources
Keywords: Intensive care units-Nursing texts